2022
DOI: 10.1002/clc.23908
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on clinical outcomes among acute myocardial infarction patients undergoing early invasive treatment strategy

Abstract: Background The implications of coronavirus disease 2019 (COVID‐19) infection on outcomes after invasive therapeutic strategies among patients presenting with acute myocardial infarction (AMI) are not well studied. Hypothesis To assess the outcomes of COVID‐19 patients presenting with AMI undergoing an early invasive treatment strategy. Methods This study was a cross‐sectional, retrospective analysis of the National COVID Cohort Collaborative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…We included any original paper reporting the use of PCI for ACS patients infected with or without COVID-19. We excluded review papers, conference abstracts, papers that include only COVID-19 patients without a comparator to negative controls, papers that included ACS patients with a past history of COVID-19 without indicating the COVID-19 status before the procedure 17 , papers with sample size less than 10 and duplicated papers. Outcomes of interest were extracted from included papers in a pre-made excel form.…”
Section: Methodsmentioning
confidence: 99%
“…We included any original paper reporting the use of PCI for ACS patients infected with or without COVID-19. We excluded review papers, conference abstracts, papers that include only COVID-19 patients without a comparator to negative controls, papers that included ACS patients with a past history of COVID-19 without indicating the COVID-19 status before the procedure 17 , papers with sample size less than 10 and duplicated papers. Outcomes of interest were extracted from included papers in a pre-made excel form.…”
Section: Methodsmentioning
confidence: 99%
“…The respective incidence rate ratios for ischemic stroke were 2.97 (1.71–5.15) in the first week, 2.80 (1.60–4.88) in the second week, and 2.10 (1.33–3.32) in weeks 3 and 4 following COVID-19. Additionally, the American retrospective analysis of COVID-19 patients with a diagnosis of acute AMI registered in the National COVID Cohort Database revealed that COVID-19 patients with AMI undergoing early invasive coronary angiography had a worse prognosis compared to those without COVID-19 [ 2 ]. Impressively, in this study, nearly 80% of COVID-19 positive and negative groups with AMI had hypercholesterolemia.…”
Section: Introductionmentioning
confidence: 99%